Dynamic Event-Triggered Boundary Control for Cyber-Physical Flexible Riser Systems Subject to Spoofing Attacks - Zhang, Xin-Yu; Xie, Xiang-Peng; Park, Ju H. (IEEE transactions on automation science and engineering, 2025)
This paper investigates the dynamic event-triggered boundary control of cyber-physical flexible riser systems under spoofing attacks. It aims to dampen vibrations resulting from riser pipe deformation, alleviate the communication load, and curtail the influence of such attacks. Firstly, a novel dynamic event-triggered boundary controller is constructed by utilizing external disturbances and event-triggering strategies. This controller overcomes the complex spatio-temporal coupling phenomena in riser systems and suppresses vibrations. Secondly, a controller is developed to minimize the impact of false data injection on the cyber-physical flexible riser system due to uncertain spoofing attacks. Finally, the stability of the system is mathematically analyzed to prevent the occurrence of Zeno phenomena. The simulation results further validate the effectiveness of the proposed method. Note to Practitioners-Cyber-physical flexible risers play an important role in various marine engineering and industrial fields, such as underwater oil and gas extraction, deep-sea resource exploitation, and seabed exploration. A challenge within these domains is the effective mitigation of cyber-physical riser vibrations amidst spoofing attacks, a problem that has yet to be resolved. This paper introduces a novel dynamic event-triggered boundary control strategy aimed at dampening vibrations induced by riser deformations, reducing communication overhead, and attenuating the effects of spoofing attacks. Based on PDEs, the proposed control strategy offers a solution for the regulation of flexible riser systems in forthcoming engineering endeavors.